Spine Stereotactic Body Radiotherapy to Three or More Contiguous Vertebral Levels - Dibs, Khaled; Blakaj, Dukagjin M.; Prasad, Rahul N.; Olausson, Alexander; Bourekas, Eric C.; Boulter, Daniel; Ayan, Ahmet S.; Cochran, Eric; Marras, William S.; Mageswaran, Prasath; Thomas, Evan; Lee, Hyeri; et al. (Frontiers in Oncology, 2022)
Background: With survival improving in many metastatic malignancies, spine metastases have increasingly become a source of significant morbidity; achieving durable local control (LC) is critical. Stereotactic body radiotherapy (SBRT) may offer improved LC and/or symptom palliation. However, due to setup concerns, SBRT is infrequently offered to patients with ≥3 contiguous involved levels. Because data is limited, we sought to evaluate the feasibility, toxicity, and cancer control outcomes of spine SBRT delivered to ≥3 contiguous levels. Methods: We retrospectively identified all SBRT courses delivered between 2013-2019 at a tertiary care institution for post-operative or intact spine metastases. Radiotherapy was delivered to 14-35 Gy in 1-5 fractions. Patients were stratified by whether they received SBRT to 1-2 or ≥3 contiguous levels. The primary endpoint was 1-year LC and was compared between groups. Factors associated with increased likelihood of local failure (LF) were explored. Acute and chronic toxicity was assessed. In-depth dosimetric data was collected. Results: 165 patients with 194 SBRT courses were identified (54% male, median age 61, 93% KPS ≥70, median follow-up 15 months). 113 patients (68%) received treatment to 1-2 and 52 to 3-7 (32%) levels. 1-year LC was 88% (89% for 1-2 levels vs 84% for ≥3 levels, p=0.747). On multivariate analysis, uncontrolled systemic disease was associated with inferior LC for patients with ≥3 treated levels. No other demographic, disease, treatment, or dosimetric variables achieved significance. Rates of new/progressive fracture were equivalent (8% vs 9.5%; p=0.839). There were no radiation induced myelopathy or grade 3+ acute or late toxicities in either group. Coverage of ≥95% of the PTV with ≥95% prescription dose was similar between groups (96% 1-2 levels vs 89% ≥3 levels, p=0.078). Conclusions: For patients with ≥3 contiguous involved levels, spine SBRT is feasible and may offer excellent LC without significant toxicity. Prospective evaluation is warranted.